Aktywność internetowa a poczucie alienacji młodzieży ery mediów - WASYLEWICZ, MAGDALENA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Magdalena Wasylewicz, Aktywność internetowa a poczucie alienacji młodzieży ery mediów [Internet activity and the sense of alienation of young people in the media era]. Interdyscyplinarne Konteksty Pedagogiki Specjalnej, nr 23, Poznań 2018. Pp. 161-176. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.23.09 The media have become man's natural environment. The younger generation matures in a highly developed society, and the media provide young people with the opportunity to meet fundamental needs, including those of people-to-people contacts. But is it for sure? This raises the question of the link between the Internet activity of young people and their sense of alienation. The article is an attempt to answer this problem. The research was carried out using the diagnostic survey method among 196 students of secondary schools in Podkarpackie and Małopolskie voivodship.